Clinical characteristics and blood/serum bound prognostic biomarkers in advanced pancreatic cancer treated with gemcitabine and nab-paclitaxel - Blomstrand, Hakon (BMC Cancer, 2020)
BACKGROUND: In recent years treatment options for advanced pancreatic cancer have markedly improved, and a combination regimen of gemcitabine and nab-paclitaxel is now considered standard of care in Sweden and elsewhere. Nevertheless, a majority of patients do not respond to treatment. In order to guide the individual patient to the most beneficial therapeutic strategy, simple and easily available prognostic and predictive markers are needed. METHODS: The potential prognostic value of a range of blood/serum parameters, patient-, and tumour characteristics was explored in a retrospective cohort of 75 patients treated with gemcitabine/nab-paclitaxel (Gem/NabP) for advanced pancreatic ductal adenocarcinoma (PDAC) in the South Eastern Region of Sweden. Primary outcome was overall survival (OS) while progression free survival (PFS) was the key secondary outcome. RESULT: Univariable Cox regression analysis revealed that high baseline serum albumin (> 37 g/L) and older age (> 65) were positive prognostic markers for OS, and in multivariable regression analysis both parameters were confirmed to be independent prognostic variables (HR 0.48, p = 0.023 and HR = 0.47, p = 0.039,). Thrombocytopenia at any time during the treatment was an independent predictor for improved progression free survival (PFS) but not for OS (HR 0.49, p = 0.029, 0.54, p = 0.073), whereas thrombocytopenia developed under cycle 1 was neither related with OS nor PFS (HR 0.87, p = 0.384, HR 1.04, p = 0.771). Other parameters assessed (gender, tumour stage, ECOG performance status, myelosuppression, baseline serum CA19–9, and baseline serum bilirubin levels) were not significantly associated with survival. CONCLUSION: Serum albumin at baseline is a prognostic factor with palliative Gem/NabP in advanced PDAC, and should be further assessed as a tool for risk stratification. Older age was associated with improved survival, which encourages further studies on the use of Gem/NabP in the elderly.